Effectiveness of mirror-assisted screening device in aiding pharyngitis diagnosis and raising patients’ awareness of rational antimicrobial use with related perceptions: 10.55131/jphd/2025/230318 - Watcharadamrongkun, Suntaree; Sirisinsuk, Yupadee; Pongthananikorn, Suyanee; Winit-Watjana, Win (Journal of Public Health and Development, 2025)
Antimicrobial drugs used for pharyngitis are prone to irrational use owing to ease of access to various sources and other risk factors. A mirror-assisted screening device (MASD) was developed to promote rational antimicrobial use, but it was not fully evaluated. This study aimed to assess the effectiveness of MASD in aiding the pharyngitis diagnosis and rational antimicrobial use of patients with pharyngitis and to elicit the perceptions of patients and healthcare providers about the use of MASD. A single-blinded, quasi-intervention study was conducted among Thai patients with pharyngitis attending primary care centers, called sub-district health promoting hospitals, in 10 provinces of three regions, i.e. the Eastern, Northern and North-eastern regions, during the 2019-2021 period. Eligible samples were conveniently allocated to an intervention group obtaining normal care plus MASD use or a control group receiving solely normal care. Patients in both groups completed a questionnaire pre- and post-interventions. All data were analyzed using descriptive statistics and a Chi-square test. The results showed that patients in the intervention and control groups (n = 2,031 and n = 235, respectively) were mostly female adults working in agricultural sectors in the North-eastern region. The rates of antimicrobial use in both groups were statistically different (17.0% vs. 24.7%, p = 0.004; RR 0.69, 95%CI [0.54, 0.88]); the relative risk reduction was 31.2%. Both groups had anticipated and intended needs for an antimicrobial and also requested it. They were mostly satisfied with MASD and willing to check their throat infections and antimicrobial use. The providers were also satisfied with and confident in using MASD to facilitate the diagnosis. Overall, MASD was effective as a pharyngitis diagnostic aid that helped patients raise their awareness of antimicrobial consumption. Further studies are required to evaluate the use of MASD in other primary care settings.